2023
DOI: 10.1149/1945-7111/acad2d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boron Doping Concentration on the Electrochemical Oxidation of Chlorine Using BDD Electrode

Abstract: Boron-doped diamond (BDD) electrode is an excellent candidate for anodic electrochemical oxidation of wastewater. However, higher concentrations of ClO3- and ClO4- of biotoxicity was found during chloride electrolysis using BDD electrodes compared to other electrode materials. In this study, BDD electrodes with five different boron doping concentrations were fabricated on silicon substrates using hot-filament chemical vapor deposition (HFCVD) method. The physical and electrochemical characterisation were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Li et al [9] prepared BDD electrodes with different boron doping concentrations by solid boron doping using boron trioxide as the boron source and found that the appropriate boron doping concentration helps to improve the electrochemical performance of BDD electrodes, and in their samples, the quality of boron doping is optimal and the potential window is maximum at a mass concentration of 2 g/L. More or less than this concentration will reduce its potential window.…”
Section: Electrochemical Properties Of Bdd Membranesmentioning
confidence: 99%
“…Li et al [9] prepared BDD electrodes with different boron doping concentrations by solid boron doping using boron trioxide as the boron source and found that the appropriate boron doping concentration helps to improve the electrochemical performance of BDD electrodes, and in their samples, the quality of boron doping is optimal and the potential window is maximum at a mass concentration of 2 g/L. More or less than this concentration will reduce its potential window.…”
Section: Electrochemical Properties Of Bdd Membranesmentioning
confidence: 99%